Burden of caregivers of older people in Sri Lanka: an overlooked concern in the health care system - Nirmala Rathnayake; Wedura Kannangara; Thilina Abeygunasekara; Warsha De Zoysa; Dhammika Palangasinghe; Sarath Lekamwasam (BMC Geriatrics)
Abstract Background Caring for older people has become a significant public health concern in Sri Lanka due to the growing aging population. This has placed a heavy burden on family caregivers, particularly those caring for older individuals with multiple chronic conditions. Recognizing this challenge, the present study aimed to evaluate the psychometric properties of the Sinhala version of the 10-item short form of the Burden Scale for Family Caregivers (BSFC-s) and assess caregiver burden and associated factors among caregivers of older people aged over 65 years with multimorbidity. Methods The BSFC-s was cross-culturally adapted following standard guidelines and administered to consecutively selected 178 family caregivers involved in the long-term care of older patients (aged ≥ 65 years) who were regular attendees of medical and neurology clinics at the National Hospital Galle, Sri Lanka. The validated Sinhala version of the Short Form-36 questionnaire (SF-36) was also administered simultaneously. After two weeks, 60 caregivers were re-assessed using the BSFC-s. The psychometric properties, including reliability and validity, as well as floor and ceiling effects, were evaluated. The final version of the BSFC-s was then administered to 270 informal family caregivers in the Gampaha District, Sri Lanka. Results The study revealed that the internal consistency of the Sinhala version of the BSFC-s, measured by Cronbach’s alpha, was 0.90, with item-total correlations ranging from 0.38 to 0.82. The test-retest reliability, assessed using the intra-class correlation coefficient, was 0.99 (95% CI: 0.99-1.00; p < 0.001). Principal component analysis revealed two factors explaining 65.8% of the cumulative variance. BSFC-s scores showed a strong negative correlation with SF-36 scores (r = -0.81, p < 0.001), indicating a good concurrent validity. Neither floor nor ceiling effects were observed. Among the 270 family caregivers, 78.1% reported a high level of burden, while 21.1% reported moderate burden. Caregiver burden was significantly associated with low educational level (p = 0.032), low monthly income (p = 0.041), and unemployment status (p < 0.001) of the caregiver. Conclusion The Sinhala version of the BSFC-s demonstrated strong reliability and validity, making it a suitable tool for assessing caregiver burden in Sri Lanka. Most caregivers reported high levels of subjective burden, particularly those with lower socio-demographic status. Trial registration Not applicable.